2007
DOI: 10.1021/np060633c
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Record of Meroditerpenes from Cacospongia Marine Sponges

Abstract: A new meroditerpene, (+)-isojaspic acid (1), along with two known meroditerpenes, cacospongin D (2) and jaspaquinol (3), have been isolated from a marine sponge Cacospongia. Comprehensive taxonomic identification distinguished this Cacospongia apart from morphologically similar Psammocinia. The absolute stereochemistry of 1 was elucidated on the basis of extensive 1D and 2D NMR techniques and analysis of the optical rotation versus (+)-zonarol (8), (+)-isozonarol (9), (-)-dactylosponol (10), and (+)-hyatellaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The PLE extraction has been carried out using three independent runs of three solvents, hexane, dichloromethane, and methanol, obtaining the highest percentage yield of the total organic extract in the fi rst extraction. Meroditerpenes, such as isojaspic acid, cacospongin, and jaspquinol, with antimicrobial properties against Staphylococcus epidermidis have been isolated from Cacospongia marine sponge (Rubio et al 2007 ) whereas sesquiterpenes, such as aignopsanoic acid A and methyl aignopsanoate A, which are moderately active against the parasite responsible for sleeping sickness, along with isoaignopsanoic acid have been obtained from Cacospongia mudofi jiensis (Johnson et al 2009 ) . In a recent work, the utility of methanol partitioning and PLE to extract 12 bioactive natural products (including isojaspic acid and aignopsanpic acid A) from fi ve marine sponges has been investigated.…”
Section: Applications To Invertebratesmentioning
confidence: 99%
“…The PLE extraction has been carried out using three independent runs of three solvents, hexane, dichloromethane, and methanol, obtaining the highest percentage yield of the total organic extract in the fi rst extraction. Meroditerpenes, such as isojaspic acid, cacospongin, and jaspquinol, with antimicrobial properties against Staphylococcus epidermidis have been isolated from Cacospongia marine sponge (Rubio et al 2007 ) whereas sesquiterpenes, such as aignopsanoic acid A and methyl aignopsanoate A, which are moderately active against the parasite responsible for sleeping sickness, along with isoaignopsanoic acid have been obtained from Cacospongia mudofi jiensis (Johnson et al 2009 ) . In a recent work, the utility of methanol partitioning and PLE to extract 12 bioactive natural products (including isojaspic acid and aignopsanpic acid A) from fi ve marine sponges has been investigated.…”
Section: Applications To Invertebratesmentioning
confidence: 99%
“…The meroditerpenes, isojaspic acid, cacospongin D and jaspaquinol have been isolated from a sponge of the genus Cacospongia. The bioactivity evaluation showed that the meroditerpenes isolated significantly inhibited Staphylococcus epidermidis [90].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…were collected from America Samoa and immediately preserved and stored according to our standard laboratory procedures. 14 A portion of the specimen (11.1 g) was worked up using a recently validated accelerated solvent extraction (ASE) protocol. 15 Four crude solvent extract fractions were obtained and included a water wash (extract code XFW: 2.3 g), followed by organic solvent fractions of: hexanes (extract code XFH: 0.025 g), dichloromethane (extract code XFD: 0.3 g) and methanol (extract code XFM: 1.5 g) (Scheme S1; S denotes Supporting Information).…”
Section: Resultsmentioning
confidence: 99%